Biological Effects of Black Phosphorus Nanomaterials on Mammalian Cells and Animals. Issue 6 (13th December 2022) - Zhang, Xuejiao; Donskyi, Ievgen S.; Tang, Weihao; Deng, Shuo; Liu, Daxu; Zhang, Siyu; Zhao, Qing; Xing, Baoshan
Abstract: The remarkable progress of applied black phosphorus nanomaterials (BPNMs) is attributed to BP's outstanding properties. Due to its potential for applications, environmental release and subsequent human exposure are virtually inevitable. Therefore, how BPNMs impact biological systems and human health needs to be considered. In this comprehensive Minireview, the most recent advancements in understanding the mechanisms and regulation factors of BPNMs' endogenous toxicity to mammalian systems are presented. These achievements lay the groundwork for an understanding of its biological effects, aimed towards establishing regulatory principles to minimize the adverse health impacts. Abstract : The impact of black phosphorus nanomaterials (BPNMs) on biological systems and human health is of significant concern as a result of their increased usage. The mechanisms and regulation factors of BPNMs' endogenous toxicity to mammalian systems are reviewed at the levels of body, tissues, cells, organelles, and molecules. A rule‐based machine learning model reveals that experimental methods, lateral size, and incubation time are determinants for their cell viability.